AGING AND THE PREPARATION FOR DEATH - Serra Desfilis, Emilia; Abengózar Torres, Mª Carmen (Anales de Psicología / Annals of Psychology)
From the Developmental Psychology is boarded the coping to face up to death of ones's own how is possible to prepare the subject during his life time. The transition to the can be used like a instrument of intervention and optimisation of the development in the process of aging and particularly in the last of life: the elderly.